Incidence of pressure injury in patients with moderate and severe traumatic brain injury: a systematic review - Wellingson S Paiva; Ranya Nascimento Ribeiro; Daniel Vieira de Oliveira; Regina Marcia C Sousa; Rita de Cassia A Vieira (BMJ Open)
Background Patients with moderate and severe traumatic brain injury (TBI) admitted to the intensive care unit (ICU) may develop pressure injury (PI) due to haemodynamic instability caused by the disease, lack of mobility in bed, as well as intense and prolonged compression in prominent bone areas.Objective The objective of this review is to assess the incidence and identify risk factor for the development of PI in patients with moderate and severe TBI admitted to the ICU.Method Searches were conducted in the PubMed, CINAHL, Scopus, Embase, Web of Science, Google Scholar, Trove and Open Grey databases, including all records found up to May 2023. Patients with moderate and severe TBI admitted to the ICU were included in this review.Results A total of 368 studies on PI and TBI were identified in the databases. Two authors assessed study bias and extracted data, wit. h a third reviewer as arbitrator. Six studies met the inclusion and exclusion criteria in the review. The incidence of PI varied between 6.5% and 20% among the included studies. Only two studies applied the Braden Scale, which identified stage II lesions (52.6% and 51.5%), located in the sacral region (78.9% and 54.6%). The risk factors identified in the studies for the development of PI were mechanical ventilation, TBI severity, vasoactive drugs, age, fever, use of enteral nutrition, haemoglobin levels and time to perform tracheostomy.Conclusion The incidence of PI in moderate and severe patients was similar to that found in ICU patients. There were significant differences across the various studies in the ways in which data were collected and reported.Trial registration number The protocol has been deposited in the PROSPERO repository (CRD42023428817).